Experimental and Numerical Study of Mild Steel Behaviour under Cyclic Loading with Variable Strain Ranges - Paulina Krolo; Davor Grandić; Željko Smolčić (Advances in Materials Science and Engineering)
To simulate the effect of variable strains on steel grades S275 and S355, an experimental displacement control test of plate specimens was performed. Specimens were tested under monotonic and cyclic loading according to the standard loading protocol of SAC 2000. During experimental testing, strain values were measured with an extensometer at the tapered part of the specimen. Strains obtained by the experimental tests are disproportional to the applied displacements at the ends of the specimens. This phenomenon occurs due to the imperfections of the specimen, hardening of the material, and the buckling behaviour that appears in real structures due to the high deformation experienced during earthquakes. Due to the relative simplicity and wide applicability of the Chaboche hardening model of steel, the calibration of hardening parameters based on experimental test results was conducted. For the first time, calibration of steel hardening parameters was performed following the Chaboche procedure to define the cyclic behaviour with variable strain ranges. The accuracy of the hardening model with variable strain ranges, which were simulated using ABAQUS software, was verified using the experimental results.